B lymphocytes confer immune tolerance via cell surface GARP-TGF-β complex - Caroline Wallace; Bill X. Wu; Mohammad Salem; Ephraim Ansa-Addo; Alessandra Metelli; Shaoli Sun; Gary S. Gilkeson; Mark J. Shlomchik; Bei Liu; Zihai Li (2018)
GARP, a cell surface docking receptor for binding and activating latent TGF-β, is highly expressed by platelets and activated Tregs. While GARP is implicated in immune invasion in cancer, the roles of the GARP-TGF-β axis in systemic autoimmune diseases are unknown. Although B cells do not express GARP at baseline, we found that the GARP-TGF-β complex is induced on activated human and mouse B cells by ligands for multiple TLRs, including TLR4, TLR7, and TLR9. GARP overexpression on B cells inhibited their proliferation, induced IgA class-switching, and dampened T cell-independent antibody production. In contrast, B cell-specific deletion of GARP-encoding gene Lrrc32 in mice led to development of systemic autoimmune diseases spontaneously as well as worsening of pristane-induced lupus-like disease. Canonical TGF-β signaling more readily upregulates GARP in Peyer patch B cells than in splenic B cells. Furthermore, we demonstrated that B cells are required for the induction of oral tolerance of T cell-dependent antigens via GARP. Our studies reveal for the first time to our knowledge that cell surface GARP-TGF-β is an important checkpoint for regulating B cell peripheral tolerance, highlighting a mechanism of autoimmune disease pathogenesis.